Single-cell RNA-sequencing of cellular heterogeneity and pathogenic mechanisms in paraquat-induced Parkinson's disease with depression - Yali Weng; Yu Zhang; Yinhan Li; Xinpei Lin; Zhenkun Guo; Hong Hu; Wenya Shao; Guangxia Yu; Fuli Zheng; Ping Cai; Huangyuan Li; Siying Wu (Ecotoxicology and Environmental Safety, 2024)
Parkinson's disease (PD) is among the most prevalent neurodegenerative diseases, and approximately one third of patients with PD are estimated to have depression. Paraquat (PQ) exposure is an important environmental risk factor for PD. In this study, we established a mouse model of PQ-induced PD with depression to comprehensively investigate cellular heterogeneity and the mechanisms underlying the progression of depression in the context of PD. We utilized single-cell RNA-seq (scRNA-seq) to acquire the transcriptomic atlas of individual cells from model mice and characterize the gene expression profiles in each differentially expressed cell type. We identified a specific glutamatergic neuron cluster responsible for the development of heterogeneous depression-associated changes and established a comprehensive gene expression atlas. Furthermore, functional enrichment and cell trajectory analyses revealed that the mechanisms underlying the progression of PD with depression were associated with specific glutamatergic neurons. Together, our findings provide a valuable resource for deciphering the cellular heterogeneity of PD with depression. The suggested connection between intrinsic transcriptional states of neurons and the progression of depression can provide insight into potential biomarkers and specific targets for anti-depression treatment in patients with PD. Synopsis: Our results obtained using model mice confirm the core effects of PQ exposure on glutamatergic neurons and their potential role in the development of PD with depression.